Analisa Audit E-Government Menggunakan Cobit 5 Untuk Domain Monitor, Evaluate And Access Pada Dinas Kominfo Kota Palembang - -, Nyimas Hamidah Purnama Agustriani; Sutabri, Tata (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
TheACommunicationAandAInformation Office of Palembang City is implementing E-Government services to improveApublicAservices, Aincrease efficiency, and increase transparency. This implementation aimsAtoAmakeAgovernment services more accessible to the public. The successfulAimplementationAof E-Government is not justAabout technology but also requires strong evaluation and supervisionAmechanisms. ATheseAprocesses are important to ensure that the intended goalsAof E-GovernmentAinitiativesAare met effectively. The primary objective of this study is toAevaluateAthe E-GovernmentAaudit conducted by the Palembang City Communication andAInformationATechnologyAOffice (Dinas Kominfo). This study specifically focuses on theAdomain ofAMEA withinAthe COBIT 5 framework, a widely recognized governanceAandAmanagementAframework for enterprise IT. The findings indicate that the e-GovernmentAInformation System, referencingAthe MEAAdomain, has achieved a Capability Level of 2, specificallyAManaged Process (MEA01) andAPerformed Process (MEA02 and MEA03). The target levelAto beAachieved is Level 4, orAPredictable Process. Based on a gap analysis, it isAevident thatAenhancements inACapability Level are necessary from the current state, particularlyAinAterms ofAinternal control and improvements in monitoring and evaluation processesAto align withAthe PalembangACity Smart City Master PlanA2018–2023. AA   Keywords— E-Government, COBIT 5, AMonitor, AEvaluate, andAAssessment (MEA)